Pandangan Efesus 4:11-16: Kepemimpinan Pelayanan yang Terdepan di Era Digital - Rajiman Andrianus Sirait; Timotius Sukarna; Ester Yunita Dewi (Jurnal Silih Asah, 2024)
This article explores in depth the theological view of Ephesians 4:11-16, which details the role of leadership in ministry in the midst of the dynamics of the digital age. This article provides a strong foundation for understanding the importance of leaders in the development and guidance of trust communities in the era of modern technology. By blending biblical analysis and contemporary perspectives, this article presents the idea that effective ministry leaders in the digital age need to find a balance between spiritual wisdom and technological understanding. Ephesians 4:11-16 opens the door to in-depth reflection on the role and responsibility of ministry leaders in facing the challenges and opportunities of the digital age. Today's leaders are required not only to have solid spiritual wisdom, but also a profound understanding of technology. They need to be able to guide the trust community through the ever-expanding digital world. This article suggests that ministry leaders should blend Bible principles with contemporary understanding of technology. Leaders who can respond wisely to social and technological dynamics will be better able to build and guide their communities. This balance creates room for spiritual growth while remaining connected to the reality of the digital world. Thus, this article stimulates thinking about how service leaders can be effective agents of change in the digital age, by combining intellectual wisdom and technological understanding to empower community beliefs towards sustainable relevance and impact.